Desenvolvimento de um modelo zerodimensional de uma zona para estudo dos parâmetros de combustão e desempenho de um motor de ignição por compressão - Vinicius Goncalves Rimsa (2018)
The purpose of the present work is to implement a code in MATLAB software to perform a simulation of the closed cycle of a compression ignition engine, obtaining the general parameters of performance, such as pressure curve in the cylinder, power, torque and specific consumption. The code consists in a zerodimensional simulation in which it is sought the solution of a set of ordinary differential equations that model the thermodynamic processes occurring with the gases in the cylinder of the engine. A control volume is considered, being limited by the inner walls of the cylinder and the conservation of mass and energy were applied to this volume. The gases are considered ideal and having uniform properties at all points within the control volume. Annands correlation is used to simulate the heat transfer to the cylinder walls and Wiebes Law is used to simulate the rate of burning of the air-fuel mixture. The numerical method used to solve the equations is the Euler Method. The validation/calibration of the model was done in three steps: first, for a given engine, the full load condition was fixed and the speed was varied (2000 rpm, 1800 rpm and 1700 rpm). These three points were simulated and the data obtained were compared with the experimental data. Then, for the same engine, the speed was set at 2000 rpm and the load was varied (full load, 60% full load and 40% full load). These three points were simulated and the data obtained were compared with the experimental data. Finally, the maximum power condition was set for two different engines. The data from these two points were then compared with the experimental data. The absolute percentage error (MAPE) between the simulated pressure curve and the experimentally obtained pressure curve was calculated, besides the error between the brake power given by the engine manufacturer and the brake power calculated by the simulation. For the brake power, the largest absolute error found was 3.07%. The MAPE between the curves ranged from 4.1% to 6.9%. The analysis of the values of the differences mentioned above and the fact that the simulation is completed in times of the order of seconds has led to the conclusion that the developed method/program is adequate to the proposal of providing the global performance parameters of a compression ignition engine in a practical and fast way, with low errors